OPTIMIZATION OF THE PARAMETERS OF DIGITAL FUZZY REGULATORS - Лагойда, Андрій; Лагойда, Людмила; Зварич, Галина; Матеїк, Галина (SWorldJournal, 2024)
The paper considers the problems related to the optimization of the parameters of digital Fuzzy controllers, in particular in the context of high-precision automatic control systems. Innovative methods and algorithms are used to select the optimal values